A guide to early college and dual enrollment programs : designing and implementing programs for student achievement - Olwell, Russell B., 1969- (New York, NY : Routledge, 2021)
"This is an accessible guide for school leaders and educators who seek to build, support, and expand effective early college and dual enrollment programs in their communities. One of the first books to bring together research in a practical way, this book is full of real stories, critical insights from leaders, teachers, and students, examples of what works and doesn't work, and strategies to help students successfully make an important jump in their lives, putting them on track to post-secondary education and a career. Whether you're starting a program from scratch or want to improve an existing dual enrollment and early college program, this book will provide you with the research base, tools, and resources to understand where you and your students fit into the national landscape, and provide guidance and inspiration on the journey to creating an effective program"--
OCLC-licensed vendor bibliographic record.
Keywords: Dual enrollment -- United States; College preparation programs -- United States; Gifted children -- Education (Secondary) -- United States; College credits -- United States; EDUCATION / Leadership